Penile compression clamps: A model of the internal mechanical state of penile soft tissues. Issue 6 (15th November 2016) - Levy, Ayelet; Fader, Mandy; Bader, Daniel; Gefen, Amit
Abstract : Aims: Prostate cancer is the most frequently diagnosed male cancer and urinary incontinence represents a major consequence following surgery. Penile compression clamps (PCCs) which externally occlude the urethra may be used to manage the incontinence. Despite potential complication of PCCs, such as deformation‐inflicted tissue damage, to date, there are no reported biomechanical criteria for design of PCCs, in terms of quantitative parameters for evaluating the safety‐versus‐efficacy of existing or future designs. Methods: We developed a set of computational three‐dimensional models of the penis, to which compression was applied using five generic PCC designs. The internal mechanical states of the soft tissues of the penis were then analysed using finite element simulations. Results: Stresses in skin, fat, and tunica albuginea regularly exceeded 10 kPa (75 mmHg). Cuff‐type and knurl‐type PCCs pose the highest potential risks to tissue health with elevated tissue stresses around the entire penile perimeter (cuff) or urethral stress concentrations (knurl). The soft and contoured PCCs produced the lowest values of these mechanical parameters. Conclusions: The present study identified design characteristics, including envelopment, adaptability, and durability which provide the safest mechanical conditions in the penis and thus minimize the risk of tissue damage while still managing incontinence. Such data should help to design a safer clamp.